Darwin’s Other Dilemmas and the Theoretical Roots of Emotional Connection - Ludwig, Robert J.; Welch, Martha G. (Frontiers in Psychology, 2019)
Modern scientific theories of emotional behavior, almost without exception, trace their origin to Charles Darwin, and his publications On the Origin of Species (1859) and The Expression of the Emotions in Man and Animals (1872). The most famous evolutionary dilemma Darwin acknowledged as a challenge to his theory of natural selection was the incomplete sub Cambrian fossil record. However, Darwin struggled with two other rarely referenced theoretical and scientific dilemmas that confounded his theories about emotional behavior. These included (1) the origin of social instincts (e.g., altruism, empathy, reciprocity and cooperation) and the reasons for their conservation in evolution and (2) the peripheral control of heart rate vis-a-vis emotional behavior outside of consciousness. Darwin acknowledged that social instincts are critical to the survival of some species, but had difficulty aligning them with his theory of natural selection in humans. Darwin eventually proposed that heart rate and emotions are controlled via one’s intellect and cortical mechanisms, and that instinctive behavior is genetically-programmed and inherited. Despite ongoing efforts, these two theoretical dilemmas are debated to this day. Simple testable hypotheses have yet to emerge for the biological mechanisms underlying instinctive behavior or the way heart rate is controlled in infants. In this paper, we review attempts to resolve ¬these issues over the past 160 years. We posit that research and theories that supported Darwin’s individualistic brain-centric and genetic model have become an “orthodox” Western view of emotional behavior, one that produced the prevailing behavioral construct of attachment as developed by John Bowlby. We trace research and theories that challenged this orthodoxy at various times, and show how these challenges were repeatedly overlooked, rejected, or misinterpreted. We review two new testable theories, emotional connection theory and calming cycle theory, which we argue resolve the two dilemmas We show emerging scientific evidence from physiology and a wide variety of other fields, as well from clinical trials among prematurely born infants, that supports the two theories. Clinical implications of the new theories and possible new ways to assess risk and intervene in emotional, behavioral and developmental disorders are discussed.